The missing mummy - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2001)
Dink, Josh, and Ruth Rose help catch the thieves who have stolen the treasure from the museum's mummy exhibit.
"A Stepping Stone book."
"M"--Spine.
3.9
3-6
Keywords: Mystery and detective stories; Stealing -- Fiction; Mystery fiction; Theft -- Fiction